Bromination: Bromination: An Alternative Strategy for Non‐Fullerene Small Molecule Acceptors (Adv. Sci. 9/2020) - Wang, Huan (Adv Sci (Weinh), 2020)
In article number https://doi.org/10.1002/advs.201903784, Feng He and co‐workers report a bromination strategy for efficient non‐fullerene acceptors with solar conversion efficiency over 16%. The single crystal structures reveal that these brominated acceptors exhibit good planarity in terms of single molecular configuration. The multiple inter‐locked Br‐S and Br‐π interactions allow them to form 3D interpenetrating networks with more charge transfer junctions. [Image: see text]